Peningkatan Imunitas Keluarga dan Budaya Kewirausahaan Masa Pandemi Covid-19 melalui Budidaya Toga di Desa Tempursari, Candimulyo, Magelang - Retno Rusdidjati; Alfian Syarifuddin; Oesman Raliby; Agus Suprapto (Jurnal Pengabdian Pada Masyarakat, 2021)
INCREASING FAMILY IMMUNITY AND ENTREPRENEURSHIP CULTURE DURING THE COVID-19 PANDEMIC THROUGH TOGA CULTIVATION IN TEMPURSARI VILLAGE, CANDIMULYO, MAGELANG. Regional economic development is the process of local government and society in managing potential local commodity resources. Development programs are not only seen from an economic or physical perspective, but also in the health sector. This pandemic condition needs developments in the health sector. Tempursari Village, Candimulyo District, Magelang Regency has a very good potential to develop family medicinal plants. The Program Kemitraan Wilayah (PKW) team from the University of Muhammadiyah Magelang and Untidar empowered the people of Tempursari Village to cultivate medicinal plants on demonstration plot lands owned by village treasury lands. Cultivation or planting that is done is planting pepper, lime and lemongrass. The purpose of planting is so that these plants can be used as an immune booster. The harvest results from these medicinal plants can later be processed into a preparation so that a new business unit appears in Tempursari Village, Candimulyo District, Magelang Regency.